2019
DOI: 10.1136/bmjopen-2019-029931
|View full text |Cite
|
Sign up to set email alerts
|

Association between procrastination, white-collar work and obesity in Japanese male workers: a cross-sectional study

Abstract: ObjectiveTo investigate the associations among procrastination (time inconsistency), work environment and obesity-related factors in Japanese male workers.DesignCross-sectional study.SettingData were collected at two work sites of Japanese electronics manufacturing company in 2015.Participants795 full-time male workers in a Japanese electric company, aged 35–64 years, who underwent health checkups in 2015.Main outcome measuresBody mass index (BMI), adult weight change, obesity (BMI ≥25 kg/m2), adult weight gai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 45 publications
0
9
0
1
Order By: Relevance
“…In more recent literature an increasing concern centers around socioemotional skills, especially self-control and self-regulation, with consequential poor health outcomes including obesity. Individuals with higher hyperbolic rates of discounting (hyperbolic discounting is a person's desire for an immediate reward rather than a higher-valued, delayed reward), who are considered impulsive or lacking self-control, tend to eat unhealthy food, drink too much alcohol, and to procrastinate when it comes to engaging in healthy behaviors, which together led to obesity [36][37][38] . The inability to obtain sufficient weight-loss often denies patients with kidney failure the possibility of being placed on the kidney transplant list.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In more recent literature an increasing concern centers around socioemotional skills, especially self-control and self-regulation, with consequential poor health outcomes including obesity. Individuals with higher hyperbolic rates of discounting (hyperbolic discounting is a person's desire for an immediate reward rather than a higher-valued, delayed reward), who are considered impulsive or lacking self-control, tend to eat unhealthy food, drink too much alcohol, and to procrastinate when it comes to engaging in healthy behaviors, which together led to obesity [36][37][38] . The inability to obtain sufficient weight-loss often denies patients with kidney failure the possibility of being placed on the kidney transplant list.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with higher hyperbolic rates of discounting (hyperbolic discounting is a person’s desire for an immediate reward rather than a higher-valued, delayed reward) are considered impulsive or lacking self-control, tend to eat unhealthy food, drink too much alcohol, and procrastinate when it comes to engaging in healthy behaviors, which together led to obesity. 36 , 37 , 38 The inability to obtain sufficient weight loss often denies patients with kidney failure the possibility of being placed on the kidney transplant list. If they do make it onto the transplant list, their weight may still keep them from receiving a kidney transplant.…”
Section: Discussionmentioning
confidence: 99%
“…In more recent literature it has been found that an increasing concern centers around socioemotional skills, especially self-control and selfregulation, with consequential poor health outcomes including obesity. Individuals with higher hyperbolic rates of discounting (Hyperbolic discounting is a person's desire for an immediate reward rather than a higher-valued, delayed reward), who are considered impulsive or lacking self-control, tend to eat unhealthy diets, to drink too much alcohol, and to procrastinate when it comes to engaging in healthy behaviors, which together led to obesity [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Цей феномен більш притаманний громадянам технічно розвинутих країн [7]. Доведено, що для «білих комірців» (фахівців розумової праці), схильність до прокрастинації характерна у набагато більшій мірі, ніж для працівників, які займаються фізичною діяльністю [8].…”
Section: аналіз літературиunclassified